Coal-Fired Power Plant's Air Quality Impact and Policy Implications - What Does the Ontario's Historical Data Tell Us ? - Wang, Mengrou (Université d'Ottawa | University of Ottawa, 2019)
Coal-fired power plants, as important electricity sources, accounted for 38 percent of global electricity and 9 percent of Canada’s electricity in 2017. However, the combustion of coal produces a lot of air pollutants and greenhouse gases that impose serious air quality, climate change and health risks on human beings and natural environment. Using Ontario’s historical dataset from 2010 to 2014, this paper finds that the increase of 100 Megawatt’s electricity from coal plants per hour would increase the hourly PM2.5 concentration by 0.06 ug/m3, NOx and SO2 by 0.13 ppb and 0.057 ppb significantly. It also finds that during the hours when the wind blows from the coal plants to the air pollutant monitors, the PM2.5 and NOx level would be higher. Compared to the further areas, the monitors within 50km from the coal plants have more serious PM2.5 and SO2 concentrations. This paper estimates that if Ontario would still have operated the three coal plants included in this study in 2015, it would have caused 219 heart disease deaths and 12 stroke deaths due to PM2.5 in the populous cities within 100km from the plants, in condition that the three plants generate electricity in the average hourly output level. Facing with coal plants’ air quality and health impacts, this paper suggests that for the provinces in Canada that still have coal plants, it is necessary to think about controlling the air pollutants from coal by shutting down the coal plants in the long-term, or at least relocating the plants or installing some control devices in the short-term, depending on different conditions each province has.